Sulphur Requirement of Crops in Bihar - Ahmed, S.; Jha, K.K. (Journal of Soil and Water Conservation, 2022)
Cultivators in Giriak area of Patna District and the adjoining parts of Nawadah (Gaya) District are using gypsum for groundnut. Like-wise gypsum has been in use for paddy in some parts of Shahabad. "Tip-burn" disease of paddy which occurs widely in Bihar has in the post been con-trolled partly or completely with sodium sulphate or ammonium sulphate or by improvement of drain-age conditions (Saran 1949, Mishra & Chakavarty 1955). On the other hand symptoms resembling "tipburn" have been artificially produced in paddy by using hydrogen sulphide (Rao and Ma 1965) suggesting a possible sulphide injury. This paper presents an account of the studies made in pots to determine the nature of sulphur problems associated with groundnut and paddy in Bihar.